2022
DOI: 10.48550/arxiv.2207.10246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GBDF: Gender Balanced DeepFake Dataset Towards Fair DeepFake Detection

Abstract: Facial forgery by deepfakes has raised severe societal concerns. Several solutions have been proposed by the vision community to effectively combat the misinformation on the internet via automated deepfake detection systems. Recent studies have demonstrated that facial analysis-based deep learning models can discriminate based on protected attributes. For the commercial adoption and massive roll-out of the deepfake detection technology, it is vital to evaluate and understand the fairness (the absence of any pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Like other broader AI research focusing on the issues associated with biased training data sets, deepfake detection research has identified diversity and bias problems within relevant datasets [78,84]. For example, detection techniques have been shown to be sensitive to gender, performing worse on female-based deepfakes [57] as compared to images of males. A recent systematic review of deepfake detection papers succinctly concludes that current models are sensitive to both novel or challenging conditions [74].…”
Section: Deepfake Creation and Detectionmentioning
confidence: 99%
“…Like other broader AI research focusing on the issues associated with biased training data sets, deepfake detection research has identified diversity and bias problems within relevant datasets [78,84]. For example, detection techniques have been shown to be sensitive to gender, performing worse on female-based deepfakes [57] as compared to images of males. A recent systematic review of deepfake detection papers succinctly concludes that current models are sensitive to both novel or challenging conditions [74].…”
Section: Deepfake Creation and Detectionmentioning
confidence: 99%
“…Researchers in [33] manually labelled several popular datasets with gender labels. They then created a new dataset called GBDF that was gender-balanced and included gender labels.…”
Section: Gender and Race Biases In Datasetsmentioning
confidence: 99%
“…It is important to consider newer and more innovative methods when searching for the best results, and many researchers have branched out from neural networks both to evaluate new methods entirely or to compare the results of new methods with neural network-based methods. Finally, we will survey studies that focus on the use of deepfake datasets in deepfake detection [33][34][35]. The dataset(s) used in training and testing of neural networks and other methods can have a substantial impact on results.…”
Section: Introductionmentioning
confidence: 99%